Optimization of Implantable Axial Pump to Increase Efficiency of Mechanical Circulatory Support - S. V. Gautier; A. P. Kuleshov; A. E. Efimov; I. I. Agapov; G. P. Itkin (Вестник трансплантологии и искусственных органов)
Aim. To optimize implantable axial pump to increase hydraulic efficiency and reduce blood hemolysis. Materials and methods. In this article the basic geometric parameters of impeller’s geometry (the blade’s angle, the blade’s length and the twist angle’s ratio) were investigated and optimized using methods of computer hydrodynamics. The calculations were carried out for the optimum operation of the pump at the speed of 8000 rpm. Results. The main parameters of impeller’s geometric were determined which made it possible to increase efficiency of the pump by an average of 7.5% (depending on the pump operation mode) and pressure drop of 8% on average. The value of shear stress in the flow region obtained as a result of the calculations did not exceed 147 Pa admissible from the point of view of blood hemolysis.